People's Republic of China : Detailed Assessment Report-CPSS-IOSCO Recommendations for Securities Settlement Systems and Central Counterparties. (IMF Staff Country Reports; Country Report ;, 2012)
A detailed assessment report on the observance of the Committee on Payment and Settlement Systems-International Organization of Securities Commissions recommendations for China's Securities Settlement Systems and Central Counterparties is presented. The bond market comprises the interbank bond market, the exchange bond market, and the bank counter market. The two stock exchanges, the Shanghai Stock Exchange and the Shenzhen Stock Exchange, have been established in 1990 and offer trading in the same type of securities, being shares, bonds, funds, and warrants.